Inhibition of urethral stricture by a catheter loaded with nanoparticle/ pirfenidone complexes - Meng, Wei; Jiang, Zhaosheng; Wang, Jiahao; Chen, Xiaohua; Chen, Bo; Cai, Bo; Zhou, Youlang; Ma, Limin; Guan, Yangbo (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Urethral strictures are common injurious conditions of the urinary system. Reducing and preventing urethral strictures has become a hot and challenging topic for urological surgeons and related researchers. In this study, we developed a catheter loaded with nanoparticle/pirfenidone (NP/PFD) complexes and evaluated its effectiveness at inhibiting urethral stricture in rabbits, providing more references for the clinical prevention and reduction of urethral stenosis.Methods: Twelve adult male New Zealand rabbits were selected and divided into the following four groups in a ratio of 1:1:1:1 using the random number table method: Group A, sham; Group B, urethral stricture (US); Group C, US + unmodified catheter; and Group D, US + NP/PFD catheter. On the 30th day after modelling, retrograde urethrography was performed to evaluate urethral stricture formation, and histopathological examination was performed on the tissues of the corresponding surgical site. Meanwhile, changes in the expression level of Transforming growth factor β1 (TGF-β1) in the tissues were detected by immunohistochemistry.The NP/PFD complexes adhered uniformly to the catheter surface. They remained on the surface of the catheter after insertion into the urethra. In addition, the NP/PFD complexes spread into the urethral epithelium 2 weeks after surgery.Ultimately, urethral strictures were significantly reduced with the placement of the NP/PFD complex catheter.Our catheter loaded with NP/PFD complexes effectively delivered PFD to the urethral epithelium through continuous local delivery, thereby reducing fibrosis and stricture after urethral injury, which may be associated with the inhibition of TGF-β1 expression.